Correlation between Perception with The Needs of Structured Education for Psoriasis Patients during The Pandemic of COVID-19 - Dewi Purnama Sari; Alfrina Hany; Magdalena Ayu Christanti; Aura Tasya Amalia (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2022)
The number of psoriasis patients visiting the health services during the COVID 19 pandemic is decreasing. Meanwhile, routine control is needed to maintain the prognosis education of psoriasis. The patient is suspected of having frequent problems and flares at home. Therefore, it is necessary to study the perception in assessing the need for structured education in a group of psoriasis patients. This study aimed to determine the correlation between perception with the need for structured education. Twenty psoriasis patients at General Hospital Dr. Saiful Anwar Malang were interviewed by telephone. The independent data consisted of patient perception (B-IPQ) of psoriasis, while the dependent data consisted of the need for structured education. Bivariate data showed the correlation between perception (B-IPQ) with the need for structured education, indicated by a p-value = 0.05. In conclusion, this study's perception (B-IPQ) level significantly correlates with the need for structured education. Promoting health education among people with psoriasis is essential to create a good perception of this diagnosis. Â